Politics Innovations Policy: Relations Authority Leadership In The Mobilization Of Support To Build On Innovation Policy - WIDIYAHSENO, BAMBANG (Jurnal Studi Pemerintahan, 2018)
Innovation policy, as long as it's better understood as a question of the ' novelty ' of ' acceptance ' which is characterized by more emphasis on technocracy. Ironically, because of the novelty side more noteworthy, then the sustainability of innovation does not well anticipate, and the ability of innovators to bequeath the institutional innovations are not social interactions social theories are available. This study intends to reveal the problem. Obviously, the emphasis on aspects of technocratic in the discussion of the innovation of the political dimension of innovation not well intention. Examine this can only be done in a descriptive-exploratory with the intent to excavate and interpret objectively illustrates the real conditions against the practices of innovation policy. This study focuses on innovation policy in the field of service permissions in Sragen. Data were taken from interview Governors, bureaucrats, Board members and various parties concerned. Data analysis was performed with two methods at once, that triangulation and interpretive. The study of this download argument that in order for successful policy innovation that is acceptable and continues (internalized) innovators must build relationships – power with various parties. It is recommended to researchers subsequent to review again the form and relation to other models in a variety of bureaucratic innovation that results can provide input to the head area.